Hydrothermal Alteration and Mineralization in the Grindulu River Segment, Pacitan, East Java: A Study of the Geotourism Potential of the River Area Mineralization - Kurniawan, Oki; Purwanto, Heru Sigit; Harjanto, Agus; Winarno, Edy; Fatchurohman, Dedi; Pratomo, Septyo Uji (Journal of Applied Sciences, Management and Engineering Technology, 2025)
The Grindulu River in Pacitan is one of the areas that exhibits manifestations of hydrothermal alteration and metal mineralization. However, the valuable metals found are relatively low, making it less economical to produce. This condition opens up other opportunities by utilizing the area as a natural laboratory for geological education and sustainable geotourism development. This study evaluates the potential for hydrothermal mineralization-based geotourism through geosite assessment. The study area comprises the Watupatok Formation and the Arjosari Formation, which show silicic, argillic, and propylitic alteration zones. The research methods include geological mapping, rock sampling, petrographic analysis, XRD, FA-AAS, and geosite assessment using the Kubalikova method, covering scientific, educational, aesthetic, and value-added aspects. The results show the presence of mineralization in the form of pyrite, chalcopyrite, sphalerite, and galena, with low levels of valuable metals (Au, Ag, Cu, Pb, Zn). Nevertheless, all three segments of the Grindulu River possess significant geosite value for educational and conservation purposes, with segment 2 considered the most ideal due to its superior accessibility and educational value. This study concludes that the Grindulu River is more appropriate for development as a sustainable geotourism destination based on conservation and geological education rather than mining exploitation.